2021
DOI: 10.3389/fpsyg.2021.640518
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Burden During the COVID-19 Pandemic in Germany

Abstract: After the first COVID-19 case was diagnosed in Germany, various measures limiting contact between people were introduced across the country. The implementation of these measures varied between jurisdictions and potentially had a negative impact on the psychological well-being of many people. However, the prevalence, severity, and type of symptoms of psychological burden has not been documented in detail. In the current study, we analysed various self-reported symptoms of psychological burden in a German sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The previous literature stresses that lockdown measures negatively affected the psychological well-being of individuals in many countries (see [ 3 ] for an overview). Correspondingly, in our empirical strategy, we assume that this lockdown affected the lives of large (if not all) parts of Germany’s society (see [ 31 , 47 , 48 ] for empirical support). Nevertheless, we cannot observe who complied with the rules of the lockdown or who did not.…”
Section: Methodsmentioning
confidence: 99%
“…The previous literature stresses that lockdown measures negatively affected the psychological well-being of individuals in many countries (see [ 3 ] for an overview). Correspondingly, in our empirical strategy, we assume that this lockdown affected the lives of large (if not all) parts of Germany’s society (see [ 31 , 47 , 48 ] for empirical support). Nevertheless, we cannot observe who complied with the rules of the lockdown or who did not.…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 outbreak in 2020, with shocking images of army trucks transporting coronavirus victims in Lombardy (Italy), the implementation of transmission and protection measures (i.e., lockdown, social distancing), together with a fear of contracting COVID-19, uncertainty of the future, and financial instability, had a negative impact on the population's emotional burden (WHO, 2022), especially among younger adults and women (Kunzler et al, 2021;Ma et al, 2021;Prati and Mancini, 2021;Racine et al, 2021;Schelhorn et al, 2021;Robinson et al, 2022). A systematic review by Santomauro et al (2021) estimated a global increase in major depressive disorder (Mata et al, 2021), we observed patterns of habituation over time with decreasing depression and stress and stable anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…This study used the population-based, representative DEGS1 data set, which implies a low risk of selection bias; yet, the results may not be transferrable to other settings. The DEGS1 data, which were collected from 2008 to 2011, may not fully describe current living conditions in Germany, especially the potential effects of the pandemic, which were shown in other studies, were not measured [ 41 ]. In our study, the SHAP methodology allowed for a detailed visualization of single feature attributions, which improved the understanding of the ML model.…”
Section: Discussionmentioning
confidence: 99%